Man-Eaters: Cannibalism and Queerness in the Giant–Knight Encounters of the Historia Regum Britanniae, the Roman de Brut, and the Roman de Perceforest. (2nd October 2018) - Lampitt, Matthew Siôn
ABSTRACT: This article offers new, queer readings of a series of encounters between knights and cannibal giants in medieval texts in French and Latin. After situating them in their wider literary context, it focuses on episodes from three texts concerned with the origins of the British Isles: Geoffrey of Monmouth's Historia Regum Britanniae ( ca .1136–38), Wace's Roman de Brut ( ca .1150–55), and the Roman de Perceforest ( ca .1340–44). Drawing on psychoanalytic and queer theory, I argue that the encounter with the cannibal giant troubles the heterosexual courtly subject due to cannibalism's intimate relationship with queerness. Close readings reveal these encounters, from wrestling matches to armed duels, to be rich in homoerotic language and imagery. Yet, rather than merely corroborating and dramatizing the modern theory, the texts push it further in ways that ask probing questions about medieval constructions of heterosexual subjectivity, namely in their striking representations of the knights flirting back with their giant foes. Thus, cannibalism emerges from these analyses as a revealing commentary on heterosexuality and on its melancholic structure, which disavows same-sex desires that cannot, for all that, ever be fully excluded.